Reduction mammaplasty at the Department of Plastic surgery in Prague - Mĕsták, J; Hrivnáková, J; Cakrtová, M; Nejedlý, A; Tomásek, D; Korýtko, J (Acta chirurgiae plasticae, 1993)
The authors present a review of the history of surgery of hypertrophic breast at the Department of Plastic Surgery in Prague. The period from 1928 to the present time was divided into stages by the dominating surgical technique. The authors emphasize the importance of careful selection of the surgical procedure with regard to the type and grade of the defect.
Keywords: hypertrofie; Czech Republic; Humans; Hypertrophy; mamoplastika; prsy; Breast; Česká republika; ženské pohlaví; Female; lidé; Mammaplasty